若(a-b)^2=a^2+ab+b^2+m,则m等于
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 01:45:49
若(a-b)^2=a^2+ab+b^2+m,则m等于若(a-b)^2=a^2+ab+b^2+m,则m等于若(a-b)^2=a^2+ab+b^2+m,则m等于∵(a-b)²=a²-2
若(a-b)^2=a^2+ab+b^2+m,则m等于
若(a-b)^2=a^2+ab+b^2+m,则m等于
若(a-b)^2=a^2+ab+b^2+m,则m等于
∵(a-b)²=a²-2ab+b²=a²+ab+b²+m
∴m=-3ab
若a/b=2 则a*a-ab+b*b/a*a+b*b等于?
若a/b=2,求分式a*a+ab-b*b/a*a-2ab+2b*b
a/b=2 ,(a*a-ab+b*b)/(a*a+b*b)=
如果a/b=2则a*a-ab+b*b/a*a+b*b求值
a+b/2ab
2AB/A+B
a+b/2ab
若a/b+b/a=3,求a^2+ab+b^2/a^2-ab+b^2的值
ab/a+b=3 a-2ab+b/2a-3ab+2b?
4ab/b^2(a-b)=
已知a+2b=0,求a*a+2ab-b*b/2a*a+ab+b*b
(a+ab)-[(ab-2b)-a]-(-9ab),其中a+b=-7,ab=3.
若ab不等于0,且3a=b,求代数式b/3a-(-b)/a-a/2b/(-b)
(a-b)平方-2ab(b-a)
(a-b)^3+2ab(a-b)
若a+b=3 ab=-2,求a+ab+ab+b的值
a^3-ab^2 =a (a^2 -b^2) =a(a+b)(a-b)
a(a+b)(a-b)-a(a+b)(a+b),其中(a+b)=1,ab=-1/2